2006
DOI: 10.2460/ajvr.67.8.1337
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic relatedness of staphylococcal strains isolated from pustules and carriage sites in dogs with superficial bacterial folliculitis

Abstract: Coagulasepositive staphylococcal strains were heterogeneous among dogs with superficial bacterial folliculitis. In individual dogs, strains from multiple pustules were genotypically the same, and strains from pustules were genotypically the same as strains from carriage sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 34 publications
9
52
0
Order By: Relevance
“…In some studies, more than one staphylococcal species was isolated from the same lesion in dogs with superficial bacterial folliculitis. 23,[36][37][38] Therefore, it is possible that in some cases multiple staphylococcal species were present but only one was isolated. Finally, the detection of an organism at the site of a lesion does not necessarily imply pathogenicity, because only colonization may be present.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, more than one staphylococcal species was isolated from the same lesion in dogs with superficial bacterial folliculitis. 23,[36][37][38] Therefore, it is possible that in some cases multiple staphylococcal species were present but only one was isolated. Finally, the detection of an organism at the site of a lesion does not necessarily imply pathogenicity, because only colonization may be present.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus has been isolated from several sites on dogs, including the anterior nares, skin and anal region, although most studies of carriage sites have focused on S. intermedius [19,20]. It has been suggested that staphylococci are transferred from the nose and mouth of the dog to its coat by grooming and pruritic behaviours, and studies have reported S. aureus in the nares of dogs colonized at other sites [10,19]. In case reports of transmission, the dog's nares is the most frequently identified site of colonization when cultures from several sites are performed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing concern about MRSA in the community has led to recommendations for surveillance, including carriage rates in healthy dogs and cats [15]. S. aureus has been isolated from several sites on dogs, including the anterior nares, skin and anal region, although most studies of carriage sites have focused on S. intermedius [19,20]. It has been suggested that staphylococci are transferred from the nose and mouth of the dog to its coat by grooming and pruritic behaviours, and studies have reported S. aureus in the nares of dogs colonized at other sites [10,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear whether one or more clonal types of S. pseudintermedius are primarily responsible for surgical infections in dogs following orthopaedic intervention (Fazakerley et al, 2010;Paul et al, 2012;Pinchbeck et al, 2006). Despite the clonal diversity reported among S. pseudintermedius in dogs, the multidrug-resistant clonal lineage (ST71-t02-SCCmec II-III) is thought to have spread among dogs in Europe (Perreten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%